Sequence polymorphism of sucrose synthase gene in kelampayan (Neolamarckia cadamba) - Chin, Amber Yen Siew. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Neolamarckia cadamba (Roxb.) Bosser or locally known as Kelampayan possesses great economic and commercial value as its timber is often used for production of plywood, veneer, furniture and hardboard. As conventional plant selection for breeding is time consuming and costly, new approach such as single nucleotide polymorphism (SNP) has often been used as marker for molecular breeding purposes. The main objective of this study was to identify the DNA sequence variation caused by single nucleotide substitution in the sucrose synthase (SuSy) gene of Kelampayan. In order to do this, DNA extracted from six Kelampayan trees were firstly subjected to polymerase chain reaction to obtain the desired SuSy sequence. BLASTn analysis was then performed to the -800 bp SuSy amplicons to search for sequence homology against non-redundant nucleotide database available in NCB!. This was followed by sequence alignment using CLC Free Workbench 6.0 for detection of SNPs. Consensus sequence of SuSy was later subjected to in silico restriction analysis. A total number of 54 SNP had been detected in the partial sucrose synthase sequence. 46 SNPs are located in the predicted coding region while 8 SNPs are positioned in the predicted non-coding region. Six restriction enzymes which include Eael, HpyCH4111, BsaBI, BpulOI, Hincll and HinPlI were detected for six SNP sites in partial sucrose synthase sequence as wei\. The effectiveness of such restriction enzyme can later be used in the development of useful genetic marker.